2006
DOI: 10.1177/0020764006067186
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Spouses of Mentally Ill People

Abstract: Better treatment, professional support and participation in self-help and advocacy groups may help to improve the quality of life of spouses of mentally ill people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 10 publications
3
40
0
9
Order By: Relevance
“…However, in another Netherlands study of spouse carers of people with schizophrenia, Angermeyer et al (2006) found that psychological well-being and social relationships were negatively affected but overall quality of life was unaffected. Davis et al (2011) found that loss of intimacy in the relationship had a significant negative impact on quality of life for those caring for a spouse with Alzheimer's or Parkinson' disease.…”
Section: Discussionmentioning
confidence: 96%
“…However, in another Netherlands study of spouse carers of people with schizophrenia, Angermeyer et al (2006) found that psychological well-being and social relationships were negatively affected but overall quality of life was unaffected. Davis et al (2011) found that loss of intimacy in the relationship had a significant negative impact on quality of life for those caring for a spouse with Alzheimer's or Parkinson' disease.…”
Section: Discussionmentioning
confidence: 96%
“…Em relação à qualidade de vida, os diversos trabalhos publicados até aos dias de hoje referiram-se às propriedades psicométricas do WHOQOL (13,(17)(18)(19)(20)(21)(22) , bem como à utilização do mesmo em amostras de pacientes psiquiátricos ou em estado de internação (23)(24)(25)(26)(27) e na população idosa (28)(29)(30) . O Brasil é um país onde parcela significativa da população (14,5%) é portadora de algum tipo de deficiência (31) .…”
Section: Análise Do íNdice Da Qualidade De Vida Por Dimensõesunclassified
“…These disorders are associated with a marked impairment in the quality of life of patients and their relatives [3,4] and incur huge economic costs [5]. A Dutch population study estimated the cost of anxiety disorders in a population of 1 million to be approximately $500 million per year [6].…”
Section: Introductionmentioning
confidence: 99%